2006
DOI: 10.1111/j.1365-2648.2006.03713.x
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of pain after day surgery: patients’ experiences of three different operation types

Abstract: A large number of patients experienced severe levels of pain after day surgery. This could have resulted from a lack of knowledge about the assessment and management of pain, in which nurses play an important role. This study has highlighted that different pain trajectories are associated with different operation types, and this has important implications for the preoperative and postoperative preparation of day surgery patients as well as the role of nurses in the overall success of the day surgery process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 46 publications
2
27
0
1
Order By: Relevance
“…Prevalence of pain after orthopedic and general surgeries is consistent with recent studies in other countries [6, 7, 11, 12, 18, 2325]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Prevalence of pain after orthopedic and general surgeries is consistent with recent studies in other countries [6, 7, 11, 12, 18, 2325]. …”
Section: Discussionsupporting
confidence: 90%
“…Before the year 2010, studies reported moderate-to-severe pain scores in more than 30% of day hospital patients 24 hours after surgery [7, 10], and the overall incidence of pain after discharge was approximately 57% [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…As the major goal of patient management in day-case surgery is to promote patient comfort and satisfaction by reducing the anticipated side-effects of surgery and anaesthesia, this finding supports the promotion of patient well-being as a health care outcome [26,27]. Previously, patients have reported pain as the most common side effect of day-case surgery [28,29]. It can be concluded that health professionals have managed to treat pain satisfactorily after day-case surgery in this sample.…”
Section: Discussionsupporting
confidence: 73%
“…The major goal of patient management in daycase surgery is to promote patient comfort and satisfaction by reducing the anticipated side effects of surgery and anaesthesia. A number of studies concentrate on these side effects and comfort questions [ 26,27], especially pain [28,29] and nausea and vomiting [30]. Safety in day-case surgery operations has also been one of the main interests in these studies [31].…”
Section: Introductionmentioning
confidence: 99%
“…Based on two prior studies [15,16], we expected that fatigue and depression would be higher in the premenstrual syndrome or premenstrual dysphoric disorder (PMS) sample than in the CS, but the prediction is only for the week preceding the onset of menses. For the hernia surgery group, studies have (not surprisingly) shown that pain intensity is high for the days after surgery [17,18]; therefore, we expected greater pain intensity and pain interference in the postsurgery week compared with the CS. Finally, for the BC sample, we predicted that fatigue would be higher than fatigue in the CS the week after chemotherapy [19].…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 93%